Understanding personnel management - Stone, Thomas H. (Chicago : Dryden Press, 1982)
This book is written in a "lean" style covering only the essential functions of personnel and human resources management while omitting needless models or pedagogical devices. There are five chapters in this book. Chapter 1 discusses personnel management within the context of the personnel field. Chapter 2 describes planning and staffing functions. Part 3 focusses on functions related to employee development. Part 4 includes functions of importance to employee maintenance. and lastly part 5 addresses issues and challenges in personnel administration.
"Selected journals": p. [515]-519.
Includes bibliographical references and index.
hza 12/07/2018
Loans
Keywords: Personnel management; United States